Pengaruh Media Sosial Terhadap Produktivitas di Fasilitas Ruang Kerja : Studi Pada Kedai Kopi di Kota Cimahi, Indonesia - Azhar, Muhamad Faisal (International Journal Administration, Business & Organization, 2024)
This study aims to determine and analyze the influence of social media on productivity in workspace facilities located in coffee shops. Employing a quantitative descriptive research method, primary data were collected through questionnaires distributed to 106 respondents who use these workspaces in Cimahi City. Data analysis was conducted using simple regression to measure the relationship between social media usage and productivity levels. The results indicate that social media has a significant positive impact on productivity within coffee shop workspaces, demonstrating a strong correlation between the two variables. These findings have important implications for both the development of knowledge in productivity management and for coffee entrepreneurs. Coffee shop owners are encouraged to leverage social media as a tool to attract customers, build community engagement, and enhance interaction, all of which can contribute to increased visitor productivity. This research also opens avenues for further studies on additional factors influencing productivity in collaborative workspaces in public venues.